Chelate based phytoremediation study for attenuation of chromium toxicity stress using lemongrass: Cymbopogon flexuosus (nees ex steud.) W. Watson. Issue 13 (10th November 2018) - Patra, Deepak Kumar; Pradhan, Chinmay; Patra, Hemanta Kumar
Abstract: Chelate employed wrenching out of Chromium from contaminated soils is a comparably new technology. The pot culture experiments were carried out to study the toxicological, physiological and biochemical changes in Lemongrass using different chelators such as Ethylenediaminetetraaceticacid (EDTA), Diethylenetriaminepentaacetic acid (DTPA), Citric acid (CA) and Salicylic acid (SA) and metal ions (Fe, Mg and Zn) in Cr +6 contaminated soil. The application of heavy metal Cr induced number of adverse consequences like reduction in root/shoot length, biomass and chlorophyl content in Lemongrass plants grown in soil with Cr +6 (50mgkg −1 ). On the contrary, the growth of Lemongrass was stimulated by the addition of chelators such as EDTA, DTPA, Citric acid, salicylic acid including metal ions (Fe, Mg and Zn). The increase in proline content was associated with the synthesis of antioxidant enzymes by the applications of chelators and metal ions. The treated plants with reduced Transportation index (Ti) values indicated more root Chromium accumulation as compared to shoot. The Bio-Concentration Factor (BCF) and Total Accumulation Rate (TAR) of Chromium were elevated with the supplementation of chelators and metal ions, thus, illustrating more metal bioavailability in plants.